21st AIAA Computational Fluid Dynamics Conference 2013
DOI: 10.2514/6.2013-2830
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Points and the Nonlinear Stability of High-Order Methods for Unsteady Flow Problems on Tetrahedral Meshes

Abstract: High-order methods have the potential to efficiently generate accurate solutions to fluid dynamics problems of practical interest. However, high-order methods are less robust than lower-order methods, as they are less dissipative, making them more susceptible to spurious oscillations and aliasing driven instabilities that arise during simulations of nonlinear phenomena. An effective approach for addressing this issue comes from noting that, for nonlinear problems, the stability of high-order nodal methods is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Furthermore, Jameson, Vincent and Castonguay [18] showed that the aliasing error associated with the ESFR schemes could be minimized in 1D by choosing the solution points to be the Gaussian quadrature points. Williams, Castonguay, Vincent and Jameson [19] devised new quadrature schemes in order to enhance nonlinear stability in simplex elements (triangles and tetrahedra).…”
Section: B Energy-stable Flux Reconstruction Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Jameson, Vincent and Castonguay [18] showed that the aliasing error associated with the ESFR schemes could be minimized in 1D by choosing the solution points to be the Gaussian quadrature points. Williams, Castonguay, Vincent and Jameson [19] devised new quadrature schemes in order to enhance nonlinear stability in simplex elements (triangles and tetrahedra).…”
Section: B Energy-stable Flux Reconstruction Schemesmentioning
confidence: 99%
“…It was shown for the ESFR schemes in 1D that the error is minimized by choosing the solution points to be the Gaussian quadrature points [18]. Recently, enhanced nonlinear stability has also been achieved in simplex elements by devising new quadrature schemes [19]. Even so, the aliasing error is still present and can become significant at higher orders of approximation, so some additional control over aliasing errors is sought.…”
mentioning
confidence: 99%
“…Following [6,7,17] we will evaluate the numerical performance of our solution points by modelling an isentropic Euler vortex in a free-stream. The initial conditions for this numerical experiment are given by…”
Section: Euler Equationsmentioning
confidence: 99%
“…Following Williams we will refer to these herein as the Williams-Shunn (WS) points. Further, in [7] Williams and Jameson proceeded to analyse the points by Shunn and Ham [12] for solving unsteady flow problems on tetrahedral meshes. (In these experiments the corresponding set of WS points were used on the faces of the tetrahedra.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation